Cadmium transfer in contaminated soil-rice systems: Insights from solid-state speciation analysis and stable isotope fractionation. (15th January 2021) - Wiggenhauser, Matthias; Aucour, Anne-Marie; Bureau, Sarah; Campillo, Sylvain; Telouk, Philippe; Romani, Marco; Ma, Jian Feng; Landrot, Gautier; Sarret, Géraldine
Abstract: Initial Cadmium (Cd) isotope fractionation studies in cereals ascribed the retention of Cd and its light isotopes to the binding of Cd to sulfur (S). To better understand the relation of Cd binding to S and Cd isotope fractionation in soils and plants, we combined isotope and XAS speciation analyses in soil-rice systems that were rich in Cd and S. The systems included distinct water management (flooded vs. non-flooded) and rice accessions with (excluder) and without (non-excluder) functional membrane transporter OsHMA3 that transports Cd into root vacuoles. Initially, 13% of Cd in the soil was bound to S. Through soil flooding, the proportion of Cd bound to S increased to 100%. Soil flooding enriched the rice plants towards heavy isotopes (δ 114/110 Cd = −0.37 to −0.39%) compared to the plants that grew on non-flooded soils (δ 114/110 Cd = −0.45 to −0.56%) suggesting that preferentially light Cd isotopes precipitated into Cd sulfides. Isotope compositions in CaCl2 root extracts indicated that the root surface contributed to the isotope shift between soil and plant during soil flooding. In rice roots, Cd was fully bound to S in all treatments. The roots in the excluder rice strongly retained Cd and its lights isotopes while heavy isotopes were transported to the shoots (Δ 114/110 Cdshoot-root 0.16–0.19‰). The non-excluder rice accumulated Cd in shoots and the apparent difference in isotope composition between roots and shoots was smaller than that of the excluder rice (Δ 114/110 Cdshoot-root −0.02 to 0.08‰). We ascribe the retention of light Cd isotopes in the roots of the excluder rice to the membrane transport of Cd by OsHMA3 and/or chelating Cd–S complexes in the vacuole. Cd–S was the major binding form in flooded soils and rice roots and partly contributed to the immobilization of Cd and its light isotopes in soil-rice systems. Graphical abstract: Image 1 Highlights: Synchrotron Cd speciation and Cd isotope ratio analyses were combined to illustrate Cd transport in soil-rice systems. Soil flooding induced precipitation of Cd sulfide and enriched the rice in heavy isotopes. Rice took up light Cd isotopes, but within the rice, heavy Cd isotopes were more mobile than light Cd isotopes. Cd in roots was fully bound to S and light Cd isotopes were retained in roots. Rice accessions with disfunctional OsHMA3 transporter reduced the Cd isotope fractionation between root and shoot.